2015
DOI: 10.1227/neu.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Jugular Foramen Schwannoma

Abstract: The surgical approach selection to JFSs should be tailored individually to their extension pattern. The judicious application of endoscope-assisted retrosigmoid infralabyrinthine and transcervical techniques allow for safe and more radical removal of JFSs with a major intraosseous part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…A wide variety of approaches to the jugular foramen have been described and these can be distilled into three groups: the lateral, anterior, and posterior approaches [ 7 - 8 ]. The anterior group involves the anterior transposition of the facial nerve, osteotomy of the mandible, and drilling of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide variety of approaches to the jugular foramen have been described and these can be distilled into three groups: the lateral, anterior, and posterior approaches [ 7 - 8 ]. The anterior group involves the anterior transposition of the facial nerve, osteotomy of the mandible, and drilling of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior group involves the anterior transposition of the facial nerve, osteotomy of the mandible, and drilling of the temporal bone. These approaches are used mainly in combination with other intracranial approaches for jugular foramen tumors with extensive extracranial involvement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides access between the labyrinthine area and the dome of the jugular bulb, laterally exposing the jugular foramen, whereas the hearing function is still at risk. Endoscopic techniques have been proposed that require drilling of the suprajugular bone using a technique similar to the access to the internal auditory canal in patients with vestibular schwannomas [24,27]. In our series, we mainly counted on the classic retrosigmoid technique and its extension, the ELITE approach, with satisfactory results.…”
Section: Choosing a Suitable Approachmentioning
confidence: 97%
“…Most JFSs are resected through the lateral or posterior trajectory. Al-Mefty et al and Samii et al argued that hearing improvements can be observed following JFS surgery [24,25]; therefore, techniques causing hearing loss may be avoided (e.g., a translabyrinthine approach). The preferred surgical approaches for JFSs have progressed to the more precise removal of the affected structures, as we show in our series.…”
Section: Choosing a Suitable Approachmentioning
confidence: 99%